TrackStudio Virtual Environments for an Integrated Toolkit for Markerless Tracking - Hristo Dimitrov (13762297) (2025)
TrackStudio is a toolkit aimed at a user-friendly and code-free markerless tracking motion capture aimed to remove barriers for people without coding experience. The files here are the toolkit's pre-packaged virtual environments that are needed for its installation and usage. Download these files in the folder where you have downloaded the code files from the GitHub repository. Once both the code files and the virtual environment has been downloaded in the same folder, double-click "Install_TrackStudio.bat" to install the toolkit (it should take approximately 20-45mins). Once installed, double-click "TrackStudio.vbs" to launch the TrackStudio toolkit. For installation and usage details, please see TrackStudio's publication.